Model for measuring customer loyalty towards a service provider - Skačkauskienė, Ilona; Vilkaitė-Vaitonė, Neringa; Vojtovic, Sergej (Journal of Business Economics and Management, 2015)
The paper aims to create a valid model for measuring customer loyalty towards a service provider. Principal solutions for designing a model of loyalty measurement have emerged from the clarified role of customer loyalty and evaluation problems. The worked out solutions include selecting a proper concept (1), loyalty specification (2), determining a period necessary for loyalty measurement (3), differentiation of loyalty measurement depending on accessible data (4) and measuring a stage of loyalty (5). The conducted research referred to an example of a catering company, thus adopting an original mathematical model for the empirical measurement of customer loyalty. The obtained results have revealed that the loyalty of the customers of the investigated service provider is of an intermediate level. The findings have also showed the superiority of the proposed model for measuring the state of customer loyalty and for obtaining better solutions to the development of customer loyalty in the service industry.